2014
DOI: 10.1039/c4sm01658k
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the crossover in dynamics of the sub-Rouse modes at the same temperature as the structural α-relaxation in polymers

Abstract: The nature of the liquid-glass transition remains an unsolved fundamental problem. One aspect is the striking change in dynamics of the structural α-relaxation generally observed at a temperature T(B) above Tg in all glass-formers. More intriguing in the case of polymers is that the change of dynamics occurs not only in the structural α-relaxation but also in the sub-Rouse modes, i.e. chain modes in between the α-relaxation and the Rouse modes. However, the nature of the dynamic crossover of the sub-Rouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
3
20
0
Order By: Relevance
“…Observed in the 1984 paper is that the mean characteristic times of the two processes approach each other at low temperatures and high pressures, which is the behavior exhibited by the sub-Rouse modes and the segmental relaxation as we now know in several polymers. The explanation of this thermorheological complex behavior was given two years later in 1986 [38], and the explanation is based on n sR being smaller than n  , consistent with papers published in the the next decade [6,22,28,31,33,36]. The creep compliance data [17] of PMPS with MW=5000 g/mol enable the determination of the range of compliance contributed by the segmental -relaxation, which is given by = 5.39 × 10 −10 Pa −1 ≤̂( ) ≤ ≈ 2.82 × 10 −9 Pa −1 .…”
Section: The Sub-rouse Modes Causing the Upper Glass Transition And Rsupporting
confidence: 78%
See 1 more Smart Citation
“…Observed in the 1984 paper is that the mean characteristic times of the two processes approach each other at low temperatures and high pressures, which is the behavior exhibited by the sub-Rouse modes and the segmental relaxation as we now know in several polymers. The explanation of this thermorheological complex behavior was given two years later in 1986 [38], and the explanation is based on n sR being smaller than n  , consistent with papers published in the the next decade [6,22,28,31,33,36]. The creep compliance data [17] of PMPS with MW=5000 g/mol enable the determination of the range of compliance contributed by the segmental -relaxation, which is given by = 5.39 × 10 −10 Pa −1 ≤̂( ) ≤ ≈ 2.82 × 10 −9 Pa −1 .…”
Section: The Sub-rouse Modes Causing the Upper Glass Transition And Rsupporting
confidence: 78%
“…Experiments in bulk polymers have shown that the sub-Rouse modes are also cooperative but to a lower degree than the segmental -relaxation [17,22,[28][29][30][31][32][33], and have smaller bulk coupling parameter, n sR , than n  of the segmental -relaxation. Like the segmental -relaxation, the sub-Rouse modes are also intermolecularly cooperative, albeit to the lesser degree and with a smaller coupling parameter , than , .…”
Section: Brief Summary Of the CMmentioning
confidence: 99%
“…[15] In this context, a value above ≈ 1.2•TG sets the threshold where the inverse relationship between diffusivity and viscosity holds. [56][57][58][59] In conclusion, reported data demonstrate connections between the BCP equilibrium state and the ordering kinetic of the system. In this framework, a model system (PS-b-PMMA) along with a suitable process (SARTA) emerge as a platform for fundamental studies where a collection of various universal behavior can be simultaneously scrutinized.…”
Section: Textsupporting
confidence: 54%
“…Generally, it could be well fitted by the Vogel–Fulcher–Tamman (VFT) equation [49,50,51]: τ=τ0exp[1αf(TT0)] where τ 0 is the pre-exponential factor, α f is the thermal expansion coefficient of the fractional free volume, and T 0 is the critical temperature (or “Vogel temperature”) at which τ diverges. To reduce the uncertainty of VFT equation fitting in the limited frequency range, according to previous works, the values of ln τ 0 of the α process, sub-Rouse modes, and Rouse modes are assumed about to be −14, −10, and −6.9 s, respectively [52,53]. As shown in Figure 10, the temperature dependences of relaxation time τ for different relaxation modes are well-described by a single VFT equation.…”
Section: Resultsmentioning
confidence: 99%